Protection of Women's Rights in Marriage According to the Compilation of Islamic Law and Its Implementation in Indonesia - Nurafni, Nurafni; Akbarizan, Akbarizan; Munir, Akmal Abdul (Dinasti Research, 2025)
The issue of protecting women's rights in marriage still leaves various problems, especially regarding women's rights and their protection, especially in Islamic legal norms. Cases of domestic violence always place women as victims, the alignment between formal law and Islamic law is clear. However, the approach to resolving domestic violence against women always prioritizes a family approach and informal resolution, so that similar cases have the potential to recur. This study examines the protection of women's rights in marriage according to a compilation of Islamic law in Indonesia using a formal juridical approach and library research methods. This study found that the protection of women's rights has been comprehensively regulated in formal state law and Islamic law, but its implementation is still not optimal because in practice the protection of women's rights is still dominated by non-formal interests such as customary/cultural law, patriarchal cultural practices so that women's rights are marginalized.